Evaluating the Impact of Wordwall on Improving Students’ Vocabulary in Recount Text at SMPN 01 Gandusari - Devita Sari Nur Safitri; Dian Fadhilawati; Nita Sutanti; Hesty Puspita Sari (EDUJ : English Education Journal, 2024)
This study investigates the effectiveness of Wordwall in enhancing vocabulary related to recount texts among eighth-grade students at SMPN 01 Gandusari. Using a pre-experimental one-group pre-test and post-test design with 28 students, the research involved pre-tests, treatment, and post-tests to collect data. The validity and reliability of the test were confirmed before administering it to the respondents. Analysis using a paired sample t-test in SPSS 24.0 revealed a significant improvement in students' vocabulary scores, increasing from a pre-test average of 70.14 to a post-test average of 83.29. The results indicate that Wordwall significantly enhances students' vocabulary achievement in recount texts. The study suggests that teachers incorporate Wordwall into English lessons to make learning more engaging and compelling, potentially extending its use to other topics. Additionally, students are encouraged to review recount text materials regularly. At the same time, future research could explore student and teacher responses to Wordwall or compare its effectiveness with other language learning tools like Duolingo or Busuu.